A Comparative Dialect Analysis of Tegal and Purwokerto Ngapak Dialects: Exploring Lexical and Phonological Variations - Christine Septiana Ayu; Indah Arvianti; Didit Kurniadi (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Dialectology is a branch of linguistics that studies language variation based on geography, including dialectal differences within a language, comparing dialects between one region and another. This research aims to identify dialect differences between Tegal and Purwokerto regions, both of which use the Ngapak dialect, and also shows what makes the difference between the Ngapak Javanese dialect and the Javanese dialect in general. The method used is direct interviews with native speakers from both regions. The data obtained was analyzed to find variations in word selection, vowel and consonant changes, and certain pronunciations. The results show that although Tegal and Purwokerto use the same dialect, there are distinctive differences in word usage and phonology. This finding confirms that each region has distinctive features that aim to provide distinction, even within the scope of the same dialect. This research makes a significant contribution to the study of dialectology, particularly in exposing internal variation within a dialect that is often ignored. In socio-cultural terms, the results of this study highlight how dialects not only function as a means of communication but also as a marker of local identity and an expression of cultural diversity that enriches Indonesia's linguistic heritage.